CD 30‐positive transformed follicular lymphoma: two case reports and literature review. Issue 6 (26th June 2015) - Montes‐Moreno, Santiago; Climent, Fina; González de Villambrosía, Sonia; González Barca, Eva M; Batlle, Ana; Insunza, Andrés; Pané‐Foix, María; Colorado, Mercedes; Martin‐Sánchez, Guillermo; Espiga, Carlos Richard; Conde, Eulogio; Piris, Miguel A
Abstract : Aims: Here we report two cases of follicular lymphoma that transformed to CD30 positive diffuse large B cell lymphoma and review the literature on this topic. Results: The first case represents an example of early transformation of conventional low‐grade follicular lymphoma to CD30‐positive large B cell lymphoma. Immunoglobulin (Ig)H and cytogenetic identity was demonstrated between both components. High‐dose and auto‐stem cell transplant (SCT) was applied and complete response was achieved. The second case represents an example of d'emblee transformation of intrafollicular neoplasia to CD30‐positive large B cell lymphoma. Immunoglobulin K deleting element (IgKde) and cytogenetic identity between both phases was demonstrated. The patient was in partial response after four cycles of rituximab plus cyclophosphamide, doxorubicin, vincristine and prednisone (R‐CHOP). Conclusions: CD30 expression was found to be associated in these cases to the transformation event and could be considered a therapeutic target to add to conventional immunochemotherapeutic regimens, even in combination with auto‐SCT. We suggest looking for CD30 expression in transformed follicular lymphoma cases.